PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR AKADEMIK DALAM PENGEMBANGAN KURIKULUM DI SMA IBNU HAJAR: Kepala Sekolah; Supervisi Akademik; Pengembangan Kurikulum. - Arifin, Zainal; Rahmawati, Ima; Latifah, Marwah; Ihsan, Muzhir (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
The principal holds a strategic role as an academic supervisor in ensuring the success of curriculum development at the school level. This study aims to describe the principal's role in carrying out academic supervision that supports curriculum development at SMA Ibnu Hajar. A qualitative approach was employed using a case study method. Data collection techniques included in-depth interviews, observations, and documentation. The findings reveal that the principal of SMA Ibnu Hajar fulfills this role through monitoring lesson planning, providing continuous teacher guidance, facilitating the development of teaching materials, and evaluating curriculum implementation. The principal also demonstrates the ability to foster professional collaboration, motivate teachers, and cultivate a reflective school culture. These academic supervision strategies have proven effective in enhancing the quality of teaching and aligning the curriculum with students’ learning needs. This study contributes to a deeper understanding of effective instructional leadership and academic supervision practices that drive curriculum improvement in schools.